Analysis of The Learn Quran Tajwid Application in Tahsin Quran Learning - Alhafizh, Alviola Daffa; Nugroho, Kharis (Universitas Muhammadiyah Surakarta, 2023)
Mastering the skill of reading the Qur'an well and correctly is a basic foundation that every Muslim must have. By mastering the basics of reading, it can be a foundation for exploring other fields of knowledge in the Qur'an. Tajwid is the most important basic science that needs to be learned first from other sciences. Because the law of studying tajwid is fardhu 'ain. In reading the Qur'an, there are also many tajwid rules, for this reason, tajwid science is important so that Muslims can read the Qur'an according to the tajwid rules and good pronunciation. The problem of Muslims today is facing difficulties in learning and memorizing various types of tajwid science and how to implement them when reading the Qur'an. Most of them only have limited knowledge about tajwid science and rarely apply it. Limited material and limited time make Muslims lazy to study tajwid science. the advancement of technology and the convenience it provides, one of the applications for learning tajwid based on Android, Learn Quran Tajwid, has emerged. Learn Quran Tajwid is an application that has been certified by renowned scholars with the aim of providing convenience for those who want to learn the science of tajwid from scratch. This application provides a variety of complete lessons, starting from material that is separated by level, concise and easy to understand, and equipped with quizzes and audio that make learning the science of tajwid fun, easy, and can be anywhere. The research method used in this study is qualitative research and library research. Qualitative research is used to explore a problem or issue and library research is a research process that involves searching for knowledge materials from books, manuscripts, or other reading materials related to the research problem. The conclusion obtained is that this application is good to use, especially for people who do not have enough time to attend tahsin circles. Because this application is simple, easy, and complete for both those who have mastered it and beginners.